THE EFFECT OF STEM PRACTICES ON PRE-SERVICE TEACHERS’ BELIEFS ON NATURE OF SCIENCE, THEIR ATTITUDES TOWARDS SCIENTIFIC RESEARCH AND CONSTRUCTIVIST APPROACH - Bekir YILDIRIM; Emine ŞAHİN; Gizem TABARU (International Journal of Eurasia Social Sciences, 2017)
In this study the effect of Science, Technology, Engineering, Mathematics (STEM) practices on pre-service science teachers’ beliefs on nature of science, their attitudes towards scientific research and constructivist approach has been examined. The research has been conducted during the fall semester of the 2016-2017 academic year within the scope of the Science and Technology course which have been given at the STEM Training Laboratory of faculty of education in a university. Twenty four pre-service teachers who have attended to department of science education of the faculty of education have taken part in this study. The study is a quantitative study and the research has been conducted according to a single group pretest-posttest model from experimental design. For the analysis of the data, t-test, arithmetic mean, standard deviation have been used for dependent and independent groups. The findings which have been obtained in the light of the research, it has been statistically found that the STEM practices have a positive effect on the pre-service teachers' beliefs on nature of science and the constructivist approach. However, it has been found that there is no significant difference on attitudes towards scientific research. In short, it can be said that STEM practices have a positive effect on the pre-service teachers’ beliefs on nature of science and constructivist approach. Thereon, suggestions about STEM education have been made for pre-service teachers, teachers and academicians.